2002
DOI: 10.1002/1522-2683(200202)23:4<662::aid-elps662>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress‐induced loss of eukaryotic initiation factor 5A (eIF‐5A) in a human pancreatic cancer cell line, MIA PaCa‐2, analyzed by two‐dimensional gel electrophoresis

Abstract: Alterations of intracellular proteins during the process of heat stress-induced cell death of a human pancreatic cancer cell line, MIA PaCa-2, were investigated using two-dimensional gel electrophoresis (2-DE), agarose gel electrophoresis, and cell biology techniques. Incubation of MIA PaCa-2 at 45 degrees C for 30 min decreased the cell growth rate and cell viability without causing chromosomal DNA fragmentation. Incubation at 51 degrees C for 30 min suppressed cell growth and again led to death without DNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This is consistent with the following observations from previous studies. First, eIF5A is known to play a role in promoting cell proliferation and preventing apoptosis [24,25]. Second, we have provided evidence that human cells maintain normal rates of cell proliferation and apoptosis if cultured in biotin-deficient medium for several weeks [26,36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is consistent with the following observations from previous studies. First, eIF5A is known to play a role in promoting cell proliferation and preventing apoptosis [24,25]. Second, we have provided evidence that human cells maintain normal rates of cell proliferation and apoptosis if cultured in biotin-deficient medium for several weeks [26,36].…”
Section: Discussionmentioning
confidence: 97%
“…In the studies described below, we will repeatedly refer to eIF5A. Evidence has been provided that eIF5A plays a role in the translation of proteins that promote cell proliferation and inhibit apoptosis [24,25].…”
Section: Introductionmentioning
confidence: 94%
“…eIF5A and its hypusinated form exhibit prolonged half-lives (≥24 hours) in many mammalian cells (40,41); strikingly, however, pulsechase studies revealed that eIF5A Hyp exhibits only approximately 6 hours of half-life in primary islets and islet-derived cell lines (present study). Interestingly, in some cell types, the half-life of eIF5A acutely diminishes to as little as 30 minutes in response to stressors such as heat shock (60,61), suggesting that both the cell type and environmental conditions can significantly influence the stability of the protein. In our case, therefore, the islet β cell may represent a unique case study for eIF5A Hyp biology.…”
Section: Discussionmentioning
confidence: 99%
“…Since one of the earliest response of cells to heat stress is the translation repression and loss of active polysomal ribosomes (Panniers and Henshaw, 1984; Mariano and Siekierka, 1986; Duncan and Hershey, 1989), we wonder whether eIF5A, an essential protein that recently reported to bind translational active ribosomes (Jao and Chen, 2006), may be involved in heat induced cell death. In this regard, it can be noted that acute heat stress of pancreatic cancer cells at high temperature (51°C) has been reported to cause a decrease of eIF5A (Takeuchi et al, 2002). We therefore examined the effect of severe heat stress on the level of eIF5A in HeLa and Caco‐2 cells.…”
Section: Resultsmentioning
confidence: 99%